A new graph-based approach for document similarity using concepts of non-rigid shapes - Lopez del Alamo, Cristian (2017)
Most methods used to compare text documents are based on the space vector model; however, this model does not capture the relations between words, which is considered necessary to make better comparisons. In this research, we propose a method based on the creation of graphs to get semantic relations between words and we adapt algorithms of the theory of non-rigid 3D model analysis.